Electrochemical Impedance Spectroscopy as a Tool to Investigate the Electrochemical Interface in Detection of Huanglongbing Bacterium Using a Magnetic Nanoparticle-Based Immunosensor - Silva, Lucas M. [UNESP]; Martins, Elaine C.; Wulff, Nelson A.; Benedetti, Assis V. [UNESP]; Yamanaka, Hideko [UNESP] (Elsevier, 2025)
Electrochemical Impedance Spectroscopy (EIS) is a non-destructive technique that is sensitive to the working interface, used to monitor changes on the electrode surfaces during each construction step of electrochemical biosensors. In this study, EIS was employed to analyze the changes at the electrode/solution interface during the development of an immunosensor for the diagnosis of Huanglongbing (HLB). HLB is a devastating citrus disease of worldwide importance, caused by the uncultured bacterium Candidatus Liberibacter asiaticus (CLas) and vectored by the psyllid Diaphorina citri. Management of HLB relies on recognition of symptomatic plants and the visual diagnosis of HLB in groves is performed by observing symptoms on the leaves. The gold standard diagnosis is the quantitative polymerase chain reaction (qPCR). However, there is a need for a test less dependent on laboratory equipment and suitable for tree-side development. This work developed an impedimetric immunosensor for the detection of CLas in citrus leaf samples. An antibody specific to CLas outer membrane protein was immobilized via Schiff base reaction on the surface of iron oxide magnetic nanoparticles (mNP) modified with the aminosilane (APTES). The resultant properties of nanoparticles surface analyzed with EIS in the behavior of the electrode/solution interface enabled the understanding of kinetic processes and mass transport in the system. This, in turn, allowed the adjustment of the equivalent electrical circuit (EECs) and the correlation of interfacial events with electrical components. The developed device successfully distinguished HLB-positive from negative samples, validated by qPCR.Comparison was made of the results obtained using the proposed methodology and the gold-standard qPCR technique, revealing excellent agreement that was statistically validated.